APPLICATION OF COMPUTER IN THE ADMINISTRATION OF COLLEGES OF EDUCATION IN NIGERIA - Gani, S. S. (Sokoto Educational Review, 2013)
There is really no doubt that Computer Education and utilization are very essential not only in educational institutions but in all aspects of modern societies. This paper discusses the usage of computer in Nigerian Colleges of Education which includes checking the in and out of library materials, keeping staff confidential records as well as keeping students examination results more accurately. The paper also highlights the benefits of computer usage in Nigerian Colleges of Education such as facilitating students learning and providing opportunities for students especially those specializing in Computer Education to become system analysts, computer operators, business centre managers, software engineers and hardware engineers in their future undertaking. However, the limitation with computer usage in Nigerian Colleges of Education is that students find it difficult to understand lessons in Computer Education because they lack the basic knowledge of computer. Also, students may have the tendency to write assignments by simply downloading relevant or irrelevant information from the net. As a result of these limitations, the writer recommends that the federal and state Ministries of Education should employ well-trained personnel that can manage the computer sets provided to the colleges effectively. Also, staff in Colleges of Education should be encouraged to utilize the computer in carrying out some of their responsibilities.